Full-length autonomous transposable elements are preferentially targeted by expression-dependent forms of RNA-directed DNA methylation. Issue 1 (December 2016) - Panda, Kaushik; Ji, Lexiang; Neumann, Drexel; Daron, Josquin; Schmitz, Robert; Slotkin, R.
Abstract Background Chromatin modifications such as DNA methylation are targeted to transposable elements by small RNAs in a process termed RNA-directed DNA methylation (RdDM). In plants, canonical RdDM functions through RNA polymerase IV to reinforce pre-existing transposable element silencing. Recent investigations have identified a "non-canonical" form of RdDM dependent on RNA polymerase II expression to initiate and re-establish silencing of active transposable elements. This expression-dependent RdDM mechanism functions through RNAi degradation of transposable element mRNAs into small RNAs guided by the RNA-dependent RNA polymerase 6 (RDR6) protein and is therefore referred to as RDR6-RdDM. Results We performed whole-genome MethylC-seq in 20 mutants that distinguish RdDM mechanisms when transposable elements are either transcriptionally silent or active. We identified a new mechanism of expression-dependent RdDM, which functions through DICER-LIKE3 (DCL3) but bypasses the requirement of both RNA polymerase IV and RDR6 (termed DCL3-RdDM). We found that RNA polymerase II expression-dependent forms of RdDM function on over 20 % of transcribed transposable elements, including the majority of full-length elements with all of the domains required for autonomous transposition. Lastly, we find that RDR6-RdDM preferentially targets long transposable elements due to the specificity of primary small RNAs to cleave full-length mRNAs. Conclusions Expression-dependent forms of RdDM function to critically target DNA methylation to full-length and transcriptionally active transposable elements, suggesting that these pathways are key to suppressing mobilization. This targeting specificity is initiated on the mRNA cleavage-level, yet manifested as chromatin-level silencing that in plants is epigenetically inherited from generation to generation.